2009
DOI: 10.1093/pcp/pcp165
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Processing Enzyme plays an Essential Role in the Crystalline Structure of Glutelin in Rice Seed

Abstract: To identify the function of genes that regulate the processing of proglutelin, we performed an analysis of glup3 mutants, which accumulates excess amounts of proglutelin and lack the vacuolar processing enzyme (VPE). VPE activity in developing seeds from glup3 lines was reduced remarkably compared with the wild type. DNA sequencing of the VPE gene in glup3 mutants revealed either amino acid substitutions or the appearance of a stop codon within the coding region. Microscopic observations showed that alpha-glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 46 publications
1
76
0
3
Order By: Relevance
“…This result highlights that the vacuolar-processing enzyme involved in post-translational processing of the precursor cruciferin forms into the corresponding acid and basic 12S cruciferin subunits is functional during the very early steps of seed germination. Vacuolar-processing enzyme is essential for the correct protein storage vacuole structure and compartmentalization of SSPs, and a seedling growth delay was reported in rice vpe mutants (48,49). This indicates that SSP processing can affect early seedling development, presumably because such processing is required for the rapid use of these proteins as a source of nitrogen and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…This result highlights that the vacuolar-processing enzyme involved in post-translational processing of the precursor cruciferin forms into the corresponding acid and basic 12S cruciferin subunits is functional during the very early steps of seed germination. Vacuolar-processing enzyme is essential for the correct protein storage vacuole structure and compartmentalization of SSPs, and a seedling growth delay was reported in rice vpe mutants (48,49). This indicates that SSP processing can affect early seedling development, presumably because such processing is required for the rapid use of these proteins as a source of nitrogen and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…When protein inclusions inside PSVs appear as a crystalline lattice, they are called crystalloids. Crystalloids have been described in rice and in seeds of some dicots, such as tomato (Solanum lycopersicum) and pumpkin (Cucurbita maxima; Krishnan et al, 1986;Krishnan and White, 1995;Kumamaru et al, 2010). Besides storage proteins, crystalloids contain integral membrane proteins and lipids, which have been hypothesized to form a multilamellar membrane/lattice structure (Jiang et al, 2000;Gillespie et al, 2005;Oufattole et al, 2005).…”
Section: Aleurone Psvs Contain Inclusions Of Zeins A-globulin and Lmentioning
confidence: 99%
“…Glutelin and globulin are components of PB-II (Yamagata et al 1982), but the influence of their reduction on PB structure was different. Studies on protein-sorting mutants revealed that deficiency of protein disulfide isomerase or vacuolar processing enzyme affects PB structure (Kumamaru et al 2010, Takemoto et al 2002, Wang et al 2009). The present study showed that storage protein itself plays an important role in formation of normal PB.…”
Section: Ultrastructure Of Protein Bodies During Seed Developmentmentioning
confidence: 99%
“…The glutelin precursor mutant 3 (glup3) mutant, which also accumulates high content of 57 kDa proglutelin polypeptides and low content of the glutelin acidic and basic subunits, shows normal PB-I in appearance and round-shaped PB-II. The round-shaped PB-II doesn't show crystalline structure typical of wild-type PB-II (Kumamaru et al 2010). These mutants with altered storage protein composition arise from mutation in protein-sorting genes; the esp2 mutant is deficient in protein disulfide isomerase, and the Glup3 gene encodes vacuolar processing enzyme (Kumamaru et al 2010, Takemoto et al 2002.…”
Section: Introductionmentioning
confidence: 99%